1999
DOI: 10.1053/euhj.1998.1273
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic and morphological correlations in tetralogy of Fallot

Abstract: The position of the outlet septum in relationship to the remainder of the muscular subpulmonary infundibulum represents a hallmark of tetralogy of Fallot, permitting its differentiation from Eisenmenger ventricular septal defects and normal hearts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 13 publications
3
15
1
Order By: Relevance
“…Tetralogy of Fallot is one of the most common types of cyanotic congenital heart disease with a reported incidence of 2–2.6/10 000 live births . It is already recognized that the clinical symptoms and the need of intervention depend on the degree of the RVOTO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetralogy of Fallot is one of the most common types of cyanotic congenital heart disease with a reported incidence of 2–2.6/10 000 live births . It is already recognized that the clinical symptoms and the need of intervention depend on the degree of the RVOTO.…”
Section: Discussionmentioning
confidence: 99%
“…Tetralogy of Fallot is one of the most common types of cyanotic congenital heart disease with a reported incidence of 2-2.6/10 000 live births. 23,24 It is already recognized that the clinical symptoms and the need of intervention depend on the degree of the RVOTO. Severe obstruction to pulmonary blood flow is associated with duct-dependent pulmonary circulation, necessitating surgical or catheter-based interventional palliation soon after birth.…”
Section: Discussionmentioning
confidence: 99%
“…22.1) [2,62]. The defect results from anterior, superior the conal septum may be present without RV outflow obstruction as in Eisenmenger type VSD [59][60][61], there must also be concomitant hypertrophy and/or hypoplasia of the subpulmonary infundibulum to produce TOF morphology. The defect results from anterior, superior the conal septum may be present without RV outflow obstruction as in Eisenmenger type VSD [59][60][61], there must also be concomitant hypertrophy and/or hypoplasia of the subpulmonary infundibulum to produce TOF morphology.…”
Section: Ventricular Septal Defect Morphologymentioning
confidence: 99%
“…A similar arrangement of the muscular outlet septum as a right ventricular structure, frequently discrete from the free-standing subpulmonary muscular infundibulum, is also to be found in tetralogy of Fallot. 13 Arguments have raged for sometime as to whether the subpulmonary infundibulum is long or short in the setting of tetralogy of Fallot. 1415 Our own echocardiographic measurements, 13 along with those performed during life some time ago by Isaaz and his colleagues, 16 have shown that, when studied in series of patients, the subpulmonary infundibulum in tetralogy of Fallot is longer than in the normal heart, albeit much narrower.…”
Section: May 2000mentioning
confidence: 99%
“…13 Arguments have raged for sometime as to whether the subpulmonary infundibulum is long or short in the setting of tetralogy of Fallot. 1415 Our own echocardiographic measurements, 13 along with those performed during life some time ago by Isaaz and his colleagues, 16 have shown that, when studied in series of patients, the subpulmonary infundibulum in tetralogy of Fallot is longer than in the normal heart, albeit much narrower. In certain patients, nonetheless, the infundibulum can be short, or even absent.…”
Section: May 2000mentioning
confidence: 99%